Analysis of the efficiency of suburban passenger transportation on the Lviv railway sections - Oleh Voznyak; Pavlo Bandrivskyi (Transport Technologies)
A developed transport system ensures the population's needs in safe movement and guarantees stable functioning and development of the production sphere. Despite being consistently unprofitable, suburban transportation by railway remains attractive for many population categories. The developed railway network, the low cost of transportation, and the capacity reserve of most sections partially compensate for the existing shortcomings and contribute to further development and open new prospects for attracting additional users of transport services. The main problems of suburban passenger transport, which worsen the quality of the services provided and affect the competitiveness of railway suburban transport compared to other modes of transport, are examined in this article. During the analysis of the schedule of suburban trains departing and arriving at the Lviv station, irrational management decisions were found that left room for improvement. In addition, the load factor of rolling stock on the routes Lviv-Sambir-Sianky and Sianky-Sambir-Lviv was determined, and it dropped to 40% during the follow-up, which indicates inefficient use of rolling stock. The ratio of the time the train stays at the stops to the total duration of the route in suburban traffic is also calculated. The time on the road for the Sambir- Stryi route was 69%, and the technical speed was only 21.7 km/h. The results obtained in the article are also typical for many other monitoring areas, indicating this problem's repeatability.